2015
DOI: 10.3389/fphys.2015.00240
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain neurocircuitry associated with human reflex cardiovascular control

Abstract: Physiological homeostasis depends upon adequate integration and responsiveness of sensory information with the autonomic nervous system to affect rapid and effective adjustments in end organ control. Dysregulation of the autonomic nervous system leads to cardiovascular disability with consequences as severe as sudden death. The neural pathways involved in reflexive autonomic control are dependent upon brainstem nuclei but these receive modulatory inputs from higher centers in the midbrain and cortex. Neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 144 publications
2
56
0
7
Order By: Relevance
“…Specifically, forebrain areas can functionally interact with one another as a network to modulate visceromotor and viscerosensory functions of cell groups within the thalamus, hypothalamus, PAG and medullary regions – which govern and monitor autonomic and neuroendocrine outflow to the heart and blood vessels in coordination with behavioral actions and motivated dispositions to act (Bandler, Keay, Floyd, & Price, 2000; Öngür & Price, 2000; Saper, 2002; Ulrich-Lai & Herman, 2009). Across several recent brain-imaging studies, stressor-evoked cardiovascular changes (e.g., in BP and HR) have been reliably associated with activity changes in these forebrain and subcortical regions, consistent with invasive animal work and patient lesion studies on central cardiovascular, autonomic, and neuroendocrine control (Critchely et al, 2003; Oppenheimer & Cechetto, 2016; Shoemaker et al, 2015; Shoemaker & Goswami, 2015). Conventionally, these forebrain and subcortical regions have been referred to as components or nodes of a central autonomic network (Bennarroch, 1993; Saper, 2002) or, more inclusively, a visceral control network.…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rsupporting
confidence: 65%
See 2 more Smart Citations
“…Specifically, forebrain areas can functionally interact with one another as a network to modulate visceromotor and viscerosensory functions of cell groups within the thalamus, hypothalamus, PAG and medullary regions – which govern and monitor autonomic and neuroendocrine outflow to the heart and blood vessels in coordination with behavioral actions and motivated dispositions to act (Bandler, Keay, Floyd, & Price, 2000; Öngür & Price, 2000; Saper, 2002; Ulrich-Lai & Herman, 2009). Across several recent brain-imaging studies, stressor-evoked cardiovascular changes (e.g., in BP and HR) have been reliably associated with activity changes in these forebrain and subcortical regions, consistent with invasive animal work and patient lesion studies on central cardiovascular, autonomic, and neuroendocrine control (Critchely et al, 2003; Oppenheimer & Cechetto, 2016; Shoemaker et al, 2015; Shoemaker & Goswami, 2015). Conventionally, these forebrain and subcortical regions have been referred to as components or nodes of a central autonomic network (Bennarroch, 1993; Saper, 2002) or, more inclusively, a visceral control network.…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rsupporting
confidence: 65%
“…As detailed in recent meta-analyses and other reviews (e.g., Gianaros & Wager, 2015; Thayer et al, 2012; Myers 2016; Shoemaker & Goswami, 2015; Beissner et al 2013, Muscatell & Eisenberger), functional divisions of the anterior cingulate cortex (ACC) and adjacent medial prefrontal cortex (mPFC), insula, hippocampus, and amygdala may be viewed as a core – albeit not exclusive – components of a broader network of forebrain systems involved in mediating stressor-evoked changes in cardiovascular activity. These forebrain systems are specifically viewed to play a role in stress appraisal processes, by ascribing personal and threat-related meaning to events, contexts, and other sources of information that are encoded and experienced (Gianaros & Wager, 2015).…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, frontostriatal areas showed a suppression of rCBF during task performance, but individuals with greater progression of SBP showed increased frontostriatal rCBF during the tasks. Frontostriatal areas are known to have both excitatory and inhibitory influences on limbic areas inducing sympathetic activation with cortical inhibitory effects on excitatory striatum effects more commonly observed 31 . Insular-subcortical activation was significantly and positively related to frontostriatal activation in the current data.…”
Section: Discussionmentioning
confidence: 99%
“…Th e prefrontal cortex and subcortical areas such as the amygdala form a reciprocal inhibitory circuit (Shoemaker and Goswami 2015), the function of which is to regulate the behavioral and emotional responses to adapt the body to environmental demands and control the function of the ANS aff ecting the heart and other organs (Williams et al 2015). Th ese authors have suggested that this circuit could serve as a connection (mediated by the ANS) between the emotional and physiological processes and that its level of activity could be monitored by the HRV.…”
mentioning
confidence: 99%